CO2 Hydrogenation to CH3OH over PdZn Catalysts, with Reduced CH4 Production. Issue 23 (14th October 2020) - Ruiz Esquius, Jonathan; Bahruji, Hasliza; Taylor, Stuart H.; Bowker, Michael; Hutchings, Graham J.
Abstract: Metallic Pd, under CO2 hydrogenation conditions (>175 °C, 20 bar in this work), promotes CO formation via the reverse water gas shift (RWGS) reaction. Pd‐based catalysts can show high selectivity to methanol when alloyed with Zn, and PdZn alloy catalysts are commonly reported as a stable alternative to Cu‐based catalysts for the CO2 hydrogenation to methanol. The production of CH4 is sometimes reported as a minor by‐product, but nevertheless this can be a major detriment for an industrial process, because methane builds up in the recycle loop, and hence would have to be purged periodically. Thus, it is extremely important to reduce methane production for future green methanol synthesis processes. In this work we have investigated TiO2 as a support for such catalysts, with Pd, or PdZn deposited by chemical vapour impregnation (CVI). Although titania‐supported PdZn materials show excellent performance, with high selectivity to CH3 OH+CO, they suffer from methane formation (>0.01 %). However, when ZnTiO3 is used instead as a support medium for the PdZn alloy, methane production is greatly suppressed. The site for methane production appears to be the TiO2, which reduces methanol to methane at anion vacancy sites. Abstract : CO2 hydrogenation : The synthesis of a range of Pd and PdZn catalysts supported on TiO2, ZnO and ZnTiO3 by chemical vapour impregnation was investigated. The results obtained confirm that methanol is produced on the β−PdZn alloy phase.